(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The objective this project is to provide feasibility study of extension of PUNE metro rail in areas like Wagholi, Ranjangaon MIDC’s etc. by carrying out demand analysis, traffic survey. This extension of Pune metro rail will boost the economic growth of remote areas. The increasing level of congestion of Pune-Nagar road coupled with high private vehicle usage. This Fast growing transportation in these areas has serious effect on public health as well as surrounded ecosystem due to the increased air as well as noise pollution. An ecologically sustainable urban transport system could be obtained by the appropriate mixture of road rail transport. Implementation of such modern transport system of metro rail facility to industrial areas of Pune city is the ultimate aim of this project.